M1 Polarization Markers Are Upregulated in Basal-Like Breast Cancer Molecular Subtype and Associated With Favorable Patient Outcome - Hachim, Mahmood Yaseen; Hachim, Ibrahim Yaseen; Talaat, Iman M.; Yakout, Nada M.; Hamoudi, Rifat (Frontiers in Immunology, 2020)
Background Breast cancer heterogeneity was proposed as an essential element that plays a role in the variable degree of therapy response as well as the patient's outcome. This highlights the need for more precise subtyping methods that focus not only on the tumor cells but also investigate the profile of stromal cells as well as the immune cell infiltrate. Objectives To mine publicly available transcriptomic breast cancer datasets with well-annotated stromal and immune cells using bioinformatics and systems immunology approaches to identify novel subsets in molecular subtypes of breast cancer. Materials and Methods Transcriptomic data from 1084 breast cancer patients obtained from TCGA database were extracted and subjected to unsupervised clustering using a recently described, multi-step algorithm called Iterative Clustering and Guide-gene Selection (ICGS). For each cluster, the stromal and immune profile was investigated using ESTIMATE and CIBERSORT analytical tool. Differentially expressed genes between the identified clusters were identified and validated in silico and in vitro by immunohistochemistry in a cohort of 80 breast cancer samples. Results Seven unique sub-clusters showed distinct molecular and clinical profiles between the well-known breast cancer subtypes. Using the clustering methodology, a panel of eight genes, including NR2E1, INGX, C1QL2, POU5F1, A2ML1, ROPN1, VGLL1, FZD9 highly expressed in basal breast cancer was identified. Two of the markers, NR2E1 and FZD9, were validated using immunohistochemistry on 80 breast cancer biopsies. The systems immunology analysis showed that while the classically activated macrophages (M1) is correlated with the more aggressive basal-like breast cancer subtype, the alternatively activated macrophages (M2) showed a higher level of expression in the luminal A and luminal B subtypes. Indeed, patients with higher levels of M1 expression showed less advanced disease and better patient outcomes presented as prolonged overall survival. Conclusion Our analysis suggests that expression levels of macrophages, in addition to cells expressing a unique set of basal breast cancer-specific genes, can predict patient outcomes and overall survival.